The Impact of Positive Behavior Interventions and Supports on Teachers' Perceptions of Teaching Conditions and Student Achievement. (July 2017) - Houchens, Gary W.; Zhang, Jie; Davis, Kelly; Niu, Chunling; Chon, Kyong Hee; Miller, Stephen
Previous research suggests that Positive Behavioral Interventions and Supports (PBIS) can reduce student disciplinary office referrals and out-of-school suspensions, especially when implemented with fidelity. Existing research is mixed as to whether PBIS also contributes to improvements in student achievement, but at least one study has found that PBIS leads to improvements in teachers' perceptions of overall organizational health, an effect that may help facilitate improvements in student learning. This study uses the TELL (Teaching, Empowering, Leading, and Learning) Kentucky survey to analyze teacher perceptions of their working conditions between PBIS and non-PBIS schools, and among schools varying in level of PBIS implementation fidelity. Furthermore, because the TELL Kentucky survey has been shown to predict increases in student achievement, this study examined the relationship between PBIS implementation and student test score outcomes. Teachers in PBIS schools reported higher levels of student and faculty understanding of behavioral expectations and a stronger atmosphere of professional trust and respect. Although there were no significant differences in student achievement levels between PBIS and non-PBIS schools, analysis did reveal that student academic outcomes were significantly higher at high- and medium-fidelity PBIS schools than low-fidelity PBIS schools. Significance, limitations, and implications for practice are discussed.